Profesionalitas “Provider” (Dokter), Mutlak Adanya Sebagai Dasar Pemberi Pelayanan Kesehatan Di Masyarakat - Boedisantoso Irianto (Fakultas Hukum Universitas Mataram, 2016)
The success of health development in the country of Indonesia, can be seen from the increasing degree of our high public health and well. The reduced mortality and reduce the number of successful births and good service can be regarded as a complete success. To achieve the above, it takes a level of professionalism of health workers. Law No. 29 of 2004 on the Practice of Medicine and Law No. 36 of 2009 on the Principles of Health and Law No. 44 of 2009 concerning Hospital, has sought to produce a professional health worker. The professionalism of the absolute health workers in the health services in the community contribution.